OUTCOMES OF PROVISIONAL STENTING WITH VERSUS WITHOUT SIDE BRANCH INTERVENTION IN PATIENTS WITH BIFURCATION LESION-RELATED ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION - NASRULLAH, .; SOLANGI, AA; ABEER, .; SHAHZEB, .; SALEEM, MW; ZAHIRULLAH, . (Biological and Clinical Sciences Research Journal, 2024)
Bifurcation lesions in patients with ST-segment elevation myocardial infarction (STEMI) present a unique challenge in interventional cardiology. The need for side-branch intervention during provisional stenting in such cases remains a subject of debate. Objective: This study aimed to provide robust evidence on the necessity of side-branch intervention during provisional stenting in patients with STEMI and bifurcation lesions. Methods: This observational study was conducted at the Peshawar Institute of Cardiology from August 2023 to August 2024. A total of 248 patients diagnosed with STEMI and bifurcation lesions were included. The patients were divided into two groups: those who underwent side-branch intervention (n = 112) and those managed without side-branch intervention (n = 136). Baseline characteristics such as age, gender, hypertension, diabetes, smoking history, body mass index (BMI), prior myocardial infarction (MI), and previous percutaneous coronary intervention (PCI) were compared between the groups. Statistical analysis was performed to identify significant differences. Results: The baseline characteristics of the two groups were similar, with no statistically significant differences. The average age was 58.7 ± 10.9 years in the side-branch intervention group and 58.3 ± 11.4 years in the no-intervention group. The male proportion was also comparable between the two groups (69% vs. 71%). Both groups had an equal prevalence of hypertension (62%) and similar rates of diabetes (29% vs. 28%) and smoking history (36% vs. 34%). Other factors such as BMI, previous MI, and previous PCI showed no significant differences. Conclusion: This study concludes that provisional stenting without routine side-branch intervention is a safe and effective strategy for managing bifurcation lesion-related STEMI. Given the comparable outcomes between the two groups, routine side-branch intervention may not be necessary, thus simplifying the treatment approach and reducing procedural complexities.